MANAJEMEN SISWA DAN PENGELOLAAN KELAS DALAM PEMBELAJARAN ALQUR’AN DI PONDOK PESANTREN TAHFIDHIL QUR'AN SIROJUL 'ULUM - Novi Udhiyana (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Sirojul 'Ulum Tahfidhil Qur'an Islamic Boarding School is an institution that specifically educates students to become tahfidz Qur'an while still paying attention to the effective management aspects of education. The application of student management and class management in learning the Qur'an is very important so that the Qur'an learning process runs optimally. The Tahfidhil Qur'an program is systematically designed to ensure that students are able to memorize the Qur'an properly and correctly. Students are encouraged to memorize the Qur'an in depth with effective and structured methods. Muroja'ah activities and memorization deposits are carried out routinely to maintain the quality of students' memorization. Student management is carried out through a tiered coaching system, daily supervision, and the involvement of students in structured daily activities of the Islamic boarding school. Management of the tahfidz class is carried out by dividing memorization groups, murojaah schedules, and teaching methods that emphasize discipline, motivation, and individual approaches. The supporting factors for success are the discipline of students, the commitment of teachers, and a conducive pesantren environment. The inhibiting factors include differences in student abilities, boredom in memorizing, and limited teaching staff. Overall, the implementation of student management and classroom management at the Sirojul 'Ulum Tahfidhil Qur'an Islamic Boarding School went well and was able to create a learning atmosphere that supported the success of the tahfidz program.